Quantum cascade lasers of λ ≈ 14µm based on three-phonon-resonance design - Meng, Bo (2013)
We report the design and demonstration of ~14 μm quantum cascade lasers based on the three-phonon-resonance active region design. The as-cleaved device with 40 periods of active region and size of 3.8 mm×28μm shows ~10 mW peak power at 280 K and maximum working temperature of 295 K. Due to the Stark effect, the laser wavelength blue-shifts from 13.75 to 13.4 μm for temperature changing from 200 K to 295 K at around roll-over current density, with characteristics temperature of 440 K.